Jeremiah 34:8-22 - a call for the enactment of distributive justice? - M. D. Terblanche (Acta Theologica)
This article seeks to determine whether the author of Jeremiah 34:8-22, in his critique of the events relating to the manumission of Hebrew slaves in 589/588 BCE during Nebuchadnezzar’s siege of Jerusalem, called for the enactment of distributive justice. Since the book of Jeremiah has a very strong intertextual character, the intertextual link between Jeremiah 34:8-22 and Deuteronomy 15:1-18 is explored. When Jeremiah 34:8-22 is read through the lens of Deuteronomy 15:1-18, it is clear that brotherliness does not tolerate debt slavery. By using Deuteronomy 15:1-18 as a supplementary text to Jeremiah 34:8-22, the author inspires visions of a counter-community, in which the debt slaves should be set free and be enabled to make a fresh start.